Tinjauan Yuridis Perlindungan Hukum Nasabah Perbankan Berdasarkan Undang-Undang Nomor 21 Tahun 2011 tentang Otoritas Jasa Keuangan - Tengku Andrias Prayudha; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Banking is a financial institution that can never be separated from the problem or dispute either the bank's internal disputes and disputes between banks and customers. Along with the times timbulah reforms to the legal system, one of which is the renewal of the legal systems of banking, namely the birth of a banking institutions like the Financial Services Authority and the Deposit Insurance Agency. Shift functions of banking regulation and supervision of Bank Indonesia to the Financial Services Authority has special meaning in particular the Financial Services Authority as the receiver of the mandate in providing legal protection of customers. Previous customer protection carried out by the Institute of Consumer Dispute Resolution (BPSK) that receives customer complaints and dispute settlement. The method of this thesis is a normative juridical approach (normative legal research), specification of research is a descriptive study where the research is to discuss the principles of law. This research was conducted by examining library materials or secondary data such as legislation, books and a variety of other sources. Based on research conducted it can be concluded that Law No. 21 Year 2011 on the Financial Services Authority regulates the protection of customers which consists of a couple of aspects based on results of the review authors, namely the prevention of the loss of customers by improving customer knowledge by publishing financial literature, service customer complaints by providing facilitation customer complaints and resolve disputes between customers and banks and legal defense for customers to file a civil suit in court by the Financial Services Authority. Legal protection is an effort that shows that the law is able to provide justice for the interests of the parties. Justice is what is perceived and believed by those who receive treatment. Legal protection settings banking customers in Law Number 21 Year 2011 on the Financial Services Authority has complied fairness of some aspects of the Agreement the Bank Baku, Conditions and Mechanism of Customer Complaints Service, terms and Dispute Resolution Mechanism Through Alternative Dispute Resolution Institute (laps).Keywords: Bank, Deposit Insurance Agency, Law Number 21 Year 2011 on the Financial Services Authority.